Cold-seep ostracods from the western Svalbard margin: direct palaeo-indicator for methane seepage? - Yasuhara, Moriaki; Sztybor, Kamila; Rasmussen, Tine Lander; Okahashi, Hisayo; Sato, Runa; Tanaka, Hayato (Journal of Micropalaeontology, 2018)
Source at https://doi.org/10.5194/jm-37-139-2018 Despite their high abundance and diversity, microfossil taxa adapted to a particular chemosynthetic environment have rarely been studied and are therefore poorly known. Here we report on an ostracod species, Rosaliella svalbardensis gen. et sp. nov., from a cold methane seep site at the western Svalbard margin, Fram Strait. The new species shows a distinct morphology, different from other eucytherurine ostracod genera. It has a marked similarity to Xylocythere, an ostracod genus known from chemosynthetic environments of wood falls and hydrothermal vents. Rosaliella svalbardensis is probably an endemic species or genus linked to methane seeps. We speculate that the surface ornamentation of pore clusters, secondary reticulation, and pit clusters may be related to ectosymbiosis with chemoautotrophic bacteria. This new discovery of specialized microfossil taxa is important because they can be used as an indicator species for past and present seep environments (http: //zoobank.org/urn:lsid:zoobank.org:pub:6075FF30-29D5-4DAB-9141-AE722CD3A69B).